Asia's new battlefield : the USA, China and the struggle for the Western Pacific - Heydarian, Richard Javad (London : Zed Books, 2015)
Offers a guide to understanding the evolution of maritime territorial disputes in East Asia, exploring their legal, political-security and economic dimensions against the backdrop of a brewing Sino-American struggle for hegemony. Heydarian shows how the pivotal relationship between the USA and China has been central to prosperity and stability in the Asia-Pacific. He also examines the ways that 'small' and 'middle' powers have shaped the trajectory of tensions in the region--tensions which could ignite an international war and re-configure the global order. --From publisher description.
The great convergence : Sino-American symbiosis -- The revenge of history -- War at sea : from the motherland to the blue soil -- Between an eagle and a dragon : the tragedy of small-power politics -- THe middle powers : a game of thrones -- After hegemony : towards a Pacific community.
Includes bibliographical references (pages 325-346) and index.
Keywords: Territorial waters -- East Asia; Law of the sea -- East Asia; Jurisdiction, Territorial -- East Asia; China -- Foreign relations -- 21st century; East Asia -- Boundaries; United States -- Relations -- China; China -- Relations -- United States